Have COVID-19-Related Economic Shocks Affected the Health Levels of Individuals in the United States and the United Kingdom? - Jiang, Baozhen; Liu, Zhaohui; Shen, Rui; Huang, Leping; Tong, Yang; Xia, Yuxin (Frontiers in Public Health, 2020)
This paper introduces a health index for measuring the health level of societies during the lockdown era, i.e., for the period from March 21, 2020 to April 7, 2020. For this purpose, individual-level survey data from the "Global Behaviours and Perceptions in the COVID-19 Pandemic" dataset are considered. We focus on cases in the United States and the United Kingdom, and the data come from 11,270 and 11,459 respondents, respectively. We then use unit root tests with structural breaks to examine whether COVID-19-related economic shocks significantly affect the health levels of the United States and the United Kingdom. The empirical results indicate that the health levels in the United States and the United Kingdom are not significantly affected by the COVID-19-related economic shocks. The evidence shows that government directives (such as lockdowns) did not significantly change the health levels of these societies.